Manifestasi Budaya dan Estetika Tas Indonesia dalam Festival Tas Nusantara - Arni Sari Anggraini; Oktaviani, Oki; Adinda Cantika Lestari; Stri Agneyastra Dite (Institut Seni Indonesia Surakarta, 2024)
The bag is a tool to make it easier for someone to carry and store items. Traditional Nusantara Bags are one of the things that should be maintained. The Nusantara Bag Festival is an effort to succeed this matter. This study aims to find out how the manifestation of culture and aesthetics of traditional Indonesian bags in the Nusantara Bag Festival. This study uses a qualitative method, through directly observation of this festival, then conducts a descriptive analysis. The results of the study show that the existence of the Nusantara Bag Festival can help to promote and introduce the archipelago bags to the public, as well as help artists, artisans, and business groups engaged in the manufacture of bags..